![\left \{ {{\frac{1}{x} -\frac{1}{y}=-\frac{4}{5}} \atop {x-y=4}} \right. \left \{ {{\frac{1}{x} -\frac{1}{y}=-\frac{4}{5}} \atop {x-y=4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B%5Cfrac%7B1%7D%7Bx%7D%20-%5Cfrac%7B1%7D%7By%7D%3D-%5Cfrac%7B4%7D%7B5%7D%7D%20%5Catop%20%7Bx-y%3D4%7D%7D%20%5Cright.)
выразим х
x=4+y
и подставим в первое уравнение
![\frac{1}{4+y} -\frac{1}{y}+\frac{4}{5} = 0 |* 5y(4+y) \frac{1}{4+y} -\frac{1}{y}+\frac{4}{5} = 0 |* 5y(4+y)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%2By%7D%20-%5Cfrac%7B1%7D%7By%7D%2B%5Cfrac%7B4%7D%7B5%7D%20%3D%200%20%7C%2A%205y%284%2By%29)
4y²+5y-20-5y+16y=0
4y²+16y-20=0 |:4
y² +4y -5 = 0
D=16+20 =36
x_{1} =4+1=5;" alt="y_{1}= \frac{-4+6}{2}=1 ; =>x_{1} =4+1=5;" align="absmiddle" class="latex-formula">
x_{2} =-5+4=-1;" alt="y_{2}= \frac{-4-6}{2}=-5 ; =>x_{2} =-5+4=-1;" align="absmiddle" class="latex-formula">
Ответ: (5;1)∪(-1;-5)